2014
DOI: 10.1103/physrevlett.113.163601
|View full text |Cite
|
Sign up to set email alerts
|

Reversing the Temporal Envelope of a Heralded Single Photon using a Cavity

Abstract: We demonstrate a way to prepare single photons with a temporal envelope that resembles the time reversal of photons from the spontaneous decay process. We use the photon pairs generated from a time-ordered cascade decay: the detection of the first photon of the cascade is used as a herald for the ground-state transition resonant second photon. We show how the interaction of the heralding photon with an asymmetric Fabry-Perot cavity reverses the temporal shape of its twin photon from a decaying to a rising expo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 30 publications
2
32
0
1
Order By: Relevance
“…The relevant energy levels are depicted in Fig. 2b: two pump beams with wavelengths 795 and 762 nm excite the atoms from 5S 1/2 , F ¼ 2 to 5D 3/2 , F ¼ 3, and a subsequent ensemble-enhanced cascade decay gives rise to the time ordering necessary for obtaining exponential time envelopes 20,28,29 . Dichroic mirrors, interference filters and coupling into single mode fibres select photon pairs of wavelengths 776 nm (herald) and 780 nm (probe).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The relevant energy levels are depicted in Fig. 2b: two pump beams with wavelengths 795 and 762 nm excite the atoms from 5S 1/2 , F ¼ 2 to 5D 3/2 , F ¼ 3, and a subsequent ensemble-enhanced cascade decay gives rise to the time ordering necessary for obtaining exponential time envelopes 20,28,29 . Dichroic mirrors, interference filters and coupling into single mode fibres select photon pairs of wavelengths 776 nm (herald) and 780 nm (probe).…”
Section: Resultsmentioning
confidence: 99%
“…The cavity reflects the herald photons with a dispersive phase shift depending on the cavity resonance frequency. Tuning the cavity on resonance or far-off resonance (70 MHz) with respect to the centre frequency of the herald photon results in exponentially rising or decaying probe photons 20 . The FWM source alternates between a laser cooling interval of 140 ms, and a photon pair generation interval of 10 ms, during which we register on average 0.054 heralding events on avalanche photodetector D h .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also reviewed their applications in manipulating temporal quantum interactions between single photons and atoms, as well as in the quantum key distribution. Most recently, it was demonstrated that a single photon with time-reversed exponential growth waveform can be loaded into a single-sided Fabry Pérot cavity with near-unity ef-ficiency [102,103]. With the time-resolved quantum-state tomography [104,105], their further applications in quantum network and quantum information processing are to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…A parametric conversion process along a cascade decay channel generates timeordered photon pairs. We collect herald (776 nm) and probe (780 nm) photons via interference filters into single mode fibers [35][36][37]. Detecting photons at 776 nm then heralds single photons at 780 nm, resonant with the 87 Rb D2 transition.…”
Section: Methodsmentioning
confidence: 99%